Konsep Penataan Ruang Terbuka Publik berdasarkan Pola Aktivitas Pengguna (Studi Kasus Alun-alun Kota Bekasi) - Nur Arief Ramadhan; Wulan Dwi Purnamasari; Deni Agus Setyono (RUAS (Review of Urbanism and Architectural Studies), 2020)
Bekasi City Square is one of the public green open spaces chosen by the people of Bekasi City. However, Bekasi City Square still has problems in the provision and quality of facilities to support users' activities, such as the unavailability of trading areas, lack of lighting and security facilities, damage to children's play areas and toilets, and lack of parking facilities. Therefore, this research was conducted to formulate the physical structuring concept of Bekasi City Square. The structuring concept is produced through behavior mapping analysis, comparative analysis, good public space index analysis, and kano analysis. Behavior mapping analysis is used to determine the distribution of activities and activity actors used as input in analyzing a good public space index. Comparative analysis and good public space index analysis are used to measure physical quality and space utilization in Bekasi City Square. Kano analysis is used to determine the priority of the structuring concept carried out for each attribute. The results of this study formulated the concept of structuring the Bekasi City Square on each attribute in the form of provision of facilities, improved quality of facilities, and a diversity of facilities.